Targeting the Endoplasmic Reticulum Unfolded Protein Response to Counteract the Oxidative Stress-Induced Endothelial Dysfunction. (14th March 2018) - Amodio, Giuseppina; Moltedo, Ornella; Faraonio, Raffaella; Remondelli, Paolo
Abstract : In endothelial cells, the tight control of the redox environment is essential for the maintenance of vascular homeostasis. The imbalance between ROS production and antioxidant response can induce endothelial dysfunction, the initial event of many cardiovascular diseases. Recent studies have revealed that the endoplasmic reticulum could be a new player in the promotion of the pro- or antioxidative pathways and that in such a modulation, the unfolded protein response (UPR) pathways play an essential role. The UPR consists of a set of conserved signalling pathways evolved to restore the proteostasis during protein misfolding within the endoplasmic reticulum. Although the first outcome of the UPR pathways is the promotion of an adaptive response, the persistent activation of UPR leads to increased oxidative stress and cell death. This molecular switch has been correlated to the onset or to the exacerbation of the endothelial dysfunction in cardiovascular diseases. In this review, we highlight the multiple chances of the UPR to induce or ameliorate oxidative disturbances and propose the UPR pathways as a new therapeutic target for the clinical management of endothelial dysfunction.